2002
DOI: 10.1103/physrevlett.88.215006
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Proton Acceleration by Hot-Electron Recirculation in Thin Foils Irradiated by Ultraintense Laser Pulses

Abstract: MeV-proton production from solid targets irradiated by 100-fs laser pulses at intensities above 1x10(20) W cm(-2) has been studied as a function of initial target thickness. For foils 100 microm thick the proton beam was characterized by an energy spectrum of temperature 1.4 MeV with a cutoff at 6.5 MeV. When the target thickness was reduced to 3 microm the temperature was 3.2+/-0.3 MeV with a cutoff at 24 MeV. These observations are consistent with modeling showing an enhanced density of MeV electrons at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
188
2

Year Published

2005
2005
2011
2011

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 424 publications
(196 citation statements)
references
References 18 publications
6
188
2
Order By: Relevance
“…While the laser pulse is present, electrons generated at the laser focus are reflected from the Debye sheath built up at the target surfaces and recirculate within the target, enhancing the electrostatic fields responsible for ion acceleration. With a peak intensity of 1!10 20 W cm K2 , Mackinnon et al (2002) observed proton energies up to 24 MeV from Al targets with thickness down to 3 mm. Such an enhancement due to recirculation in thin foil targets motivates research using even thinner targets.…”
Section: Effects Of Laser Pulse Contrast On Ion Accelerationmentioning
confidence: 99%
See 2 more Smart Citations
“…While the laser pulse is present, electrons generated at the laser focus are reflected from the Debye sheath built up at the target surfaces and recirculate within the target, enhancing the electrostatic fields responsible for ion acceleration. With a peak intensity of 1!10 20 W cm K2 , Mackinnon et al (2002) observed proton energies up to 24 MeV from Al targets with thickness down to 3 mm. Such an enhancement due to recirculation in thin foil targets motivates research using even thinner targets.…”
Section: Effects Of Laser Pulse Contrast On Ion Accelerationmentioning
confidence: 99%
“…With this contrast, and a minimum pedestal duration of 1.0 ns, we observe protons with energy extending beyond 4.5 MeV, from Al target foils of thickness down to 0.2 mm. Motivated by the observed enhancement in proton numbers and energies reported by Mackinnon et al (2002), and attributed to electron recirculation within thin foils, we extend our investigation to even higher contrast and thinner targets.…”
Section: Proton Acceleration With Ultra-high Contrast Laser Pulsesmentioning
confidence: 99%
See 1 more Smart Citation
“…4 In addition, if the thickness is less than c /2 ͑ is the laser pulse duration and c the speed of light͒, electron recirculation within the target during the laser pulse may further enhance the acceleration field at the rear surface. 5 Finally, for very high intensities and ultrathin targets, relativistic transparency allows part of the laser pulse to be transmitted through the target and contribute to increased electron heating. 6 However, there are limits to this decrease in target thickness in order to optimize proton acceleration.…”
mentioning
confidence: 99%
“…When the electrons reach the rear side of the target only the fastest electrons (precursor electrons) can escape since a potential will be build up which hinder the electrons to escape. The electrons which can not escape turn around reentering the target surface and starting to oscillate [64,65]. These electrons which leak into the vacuum (as discussed in Chapter 2.3) create a so-called electron sheath.…”
Section: Target Normal Sheath Accelerationmentioning
confidence: 99%